2016
DOI: 10.1186/s40463-016-0144-4
|View full text |Cite
|
Sign up to set email alerts
|

MRI and CBCT image registration of temporomandibular joint: a systematic review

Abstract: PurposeThe purpose of the present review is to systematically and critically analyze the available literature regarding the importance, applicability, and practicality of (MRI), computerized tomography (CT) or cone-beam CT (CBCT) image registration for TMJ anatomy and assessment.Data sourcesA systematic search of 4 databases; MEDLINE, EMBASE, EBM reviews and Scopus, was conducted by 2 reviewers. An additional manual search of the bibliography was performed.Inclusion criteriaAll articles discussing the magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 30 publications
0
36
0
5
Order By: Relevance
“…The results obtained in this study are based on the analysis of MRI and CT, methods reported as gold standards for the evaluation of the structures of the TMJ 15,34 . However, CBCT is suggested as an alternative of lower radiation dose for patients 17,35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained in this study are based on the analysis of MRI and CT, methods reported as gold standards for the evaluation of the structures of the TMJ 15,34 . However, CBCT is suggested as an alternative of lower radiation dose for patients 17,35 .…”
Section: Discussionmentioning
confidence: 99%
“…For imaging evaluation of the TMJ, the MRI is considered the gold standard, since it allows obtaining soft tissue images of excellent contrast and has the advantage of being a free ionising radiation test 14‐16 . While computerised tomography (CT) is considered the most accurate of traditional radiographic techniques to obtain images of TMJ and evaluate hard tissues, 17 recently, conical beam CT (CBCT) has been developed as an alternative to conventional CT for dental and maxillofacial diagnosis, with the benefit of lower ionising radiation for the patient 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, para diagnosticar alterações intracapsulares da ATM, no que se refere ao deslocamento mandibular, podese considerar a RM como um excelente exame de imagem no diagnóstico de tal patologia 19 . Uma revisão sistemática relata que mesmo com todo o avanço da capacidade de diagnóstico da RM, a mesma apresenta baixa qualidade em suas imagens, quando se refere ao estudo dos componentes ósseos da ATM 20 . Da mesma forma, Gonçalves, Dotta e Serra (2011) afirmam que ainda é possível encontrar limitações desse exame no diagnóstico das alterações da ATM, pois a mesmo não disponibiliza de clareza de detalhes e nem de precisão dos componentes ósseos dessa articulação, sendo assim necessário o auxílio de outros exames de imagens para o estudo aprofundado desses componentes e para a obtenção de um diagnóstico mais completo de toda a estrutura articular da ATM 14 .…”
Section: Podeunclassified
“…Alguns autores ressaltam que a TCCB possui a capacidade de demonstrar achatamento da cabeça do côndilo, caracterizando-se como uma patologia que mais acomete as estruturas ósseas da ATM em pacientes crianças com artrite idiopática juvenil 20 . Em contrapartida, a TCCB limita-se apenas a avaliação dos componentes ósseos, e ao diagnóstico de alterações presentes nas estruturas ósseas da ATM, ou seja, o mesmo não é indicado para avaliar tecidos moles dessa articulação 21 .…”
Section: Podeunclassified
“…Fusing MRI and CBCT imaging have been recently introduced to assess TMJ pathology. [15] MRI and CBCT images are registered in a common spatial 3D coordinate system first before their final fusion. The fused images provide a desirable complementary information of the articular disc and osseous surfaces for optimum diagnosis.…”
Section: Introductionmentioning
confidence: 99%